2017
DOI: 10.1007/s00253-017-8449-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dust exposure on mixed bacterial cultures and during eukaryotic cell co-culture infections

Abstract: On a daily basis, humans, and their colonizing microbiome, are exposed to both indoor and outdoor dust, containing both deleterious organic and inorganic contaminants, through dermal contact, inhalation, and ingestion. Recent studies evaluating the dust exposure responses of opportunistic pathogens, such as Escherichia coli and Pseudomonas aeruginosa, revealed significant increases in biofilm formation following dust exposure. In this study, the effects of dust exposure on mixed bacterial cultures as well as H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“… 37 , 38 In addition, limited in vitro studies using human corneal epithelial cells (HCET), have suggested, but did not provide mechanisms, by which PM 2.5 may promote autophagy, 39 damage mitochondrial function, 40 decrease cell viability, 41 and cause oxidative damage. 41 If bacteria are present, exposure of mucosal sites to PM may also enhance bacterial stress resistance mechanisms, 42 , 43 biofilm formation, 42 , 43 and enhance colonization. 42 , 43 In this regard, epidemiologic studies strongly suggest that it is biologically plausible to hypothesize that exposure to PM 2.5 is associated with some of the major blinding and painful eye conditions seen worldwide, including the development of corneal ulcers resulting from delayed wound healing after injury or infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 37 , 38 In addition, limited in vitro studies using human corneal epithelial cells (HCET), have suggested, but did not provide mechanisms, by which PM 2.5 may promote autophagy, 39 damage mitochondrial function, 40 decrease cell viability, 41 and cause oxidative damage. 41 If bacteria are present, exposure of mucosal sites to PM may also enhance bacterial stress resistance mechanisms, 42 , 43 biofilm formation, 42 , 43 and enhance colonization. 42 , 43 In this regard, epidemiologic studies strongly suggest that it is biologically plausible to hypothesize that exposure to PM 2.5 is associated with some of the major blinding and painful eye conditions seen worldwide, including the development of corneal ulcers resulting from delayed wound healing after injury or infection.…”
mentioning
confidence: 99%
“… 41 If bacteria are present, exposure of mucosal sites to PM may also enhance bacterial stress resistance mechanisms, 42 , 43 biofilm formation, 42 , 43 and enhance colonization. 42 , 43 In this regard, epidemiologic studies strongly suggest that it is biologically plausible to hypothesize that exposure to PM 2.5 is associated with some of the major blinding and painful eye conditions seen worldwide, including the development of corneal ulcers resulting from delayed wound healing after injury or infection. 5 Those studies further suggest that it is difficult to study clinical disease retrospectively and that experimental models are needed to test mechanistically the relationship between PM 2.5 exposure and ocular disease and infection.…”
mentioning
confidence: 99%
“…114 While plenty of information about commonly used probiotic species is available on their capacity in the laboratory, information justifying the selection of these as probiotic species is less abundant. 114 While plenty of information about commonly used probiotic species is available on their capacity in the laboratory, information justifying the selection of these as probiotic species is less abundant.…”
Section: Pro -Microb Ial Cle Aningmentioning
confidence: 99%
“…Exposure to outdoor dust enhanced the biofilm formation of a number of bacterial pathogens as well as their ability to proliferate in co-culture with human cells. 114 While plenty of information about commonly used probiotic species is available on their capacity in the laboratory, information justifying the selection of these as probiotic species is less abundant. For example, data stemming from studies involving in vitro experimentation using dust communities or in situ experimentation in complex, occupied built environments is lacking.…”
Section: Further Environmental Context Can Alter Microbial Communitiesmentioning
confidence: 99%
“…Furthermore, previous studies have indicated that the indoor dust exposure affects the growth, bio lm formation, oxidative stress, and virulence of microorganisms [6, [21][22][23][24][25][26][27]. Unfortunately, these studies conducted under controlled conditions, and little is known about the physiological impact of dust exposure on the microorganisms.…”
Section: Introductionmentioning
confidence: 99%